ADVERTISING STRATEGIES REFLECTED IN KFC TELEVISION ADVERTISEMENTS SEEN FROM CULTURAL DIMENSIONS IN AMERICA AND VIETNAM = Chiến lược quảng cáo thể hiện trong quảng cáo truyền hình của kfc nhìn từ giá trị văn hóa ở Mĩ và Việt Nam - Dương, Thu Thảo (2020)
Today, in the globalization context, with the rapid development of technology, people are able to approach various types of advertisements whose function is to get attention, to supply information, to promote the product from both internal and external culture. This study focuses on differences of cultural values as well as advertising strategies reflected American and Vietnamese TV commercials. To investigate underlying cultural values together with advertising strategies, 3 US TV ads and 3 VN TV ads were collected. A cross-cultural framework is applied to compare and content-analyze these advertisements. After analyzing, remarkable insights into cultural reflection in television advertisements of two nations as well as preferable advertising strategies are figured out. Last but not least, the research provides some suggestions on studying crosscultural communication for English learners as well as advertising practitioners.